Exploring Determinants of Job Satisfaction among Academic Members in Jordanian Higher Education Institutions - Tawalbeh , Mohammed; Al-Khazaleh, Suhaib; Albhirat , Muath Maqbool; Tawalbeh, Jawad Haitham (International Review of Management and Marketing, 2024)
This study aimed to identify the determinants of job satisfaction among academic staff in Jordanian Higher Education Institutions and propose a model that these institutions can use to estimate overall job satisfaction. Understanding these determinants is critical for faculty retention, performance, and organizational effectiveness. This study employed a quantitative approach to examine job satisfaction and its determinants among academic members in Jordanian Higher Education Institutions. A total of 272 participants were asked to rate their level of agreement with multiple statements regarding job satisfaction determinants using a Likert scale. The data collected were analyzed to identify the key factors influencing job satisfaction among academic staff. The study found that the work environment, promotion and development opportunities, and job security are significant determinants of job satisfaction among academic staff in Jordan. These factors play a crucial role in shaping faculty members’ perspectives on their jobs and their overall satisfaction levels. The findings of this study provide valuable insights for Higher Education Institutions that aim to enhance faculty satisfaction and organizational effectiveness. By focusing on improving the work environment, offering clear promotion and development paths, and ensuring job security, institutions can retain and motivate their academic staff better.